Combined photocatalytic properties and energy efficiency via multifunctional glass. Issue 2 (April 2019) - Oladipo, Habeebllah; Garlisi, Corrado; Al-Ali, Khalid; Azar, Elie; Palmisano, Giovanni
Graphical abstract: Highlights: Thin films of TiO2 supported on glass resulted in 2-propanol abatement. Pilkington Glass stained with standard dye has been tested successfully. Double-glazed Pilkington Activ Blue was the best energy-efficient configuration. Abstract: This study reports on the photocatalytic activity and energy efficiency of two self-cleaning glass benchmarks, namely Pilkington Activ ™ Blue (PAB) and Pilkington Activ ™ Clear (PAC). These self-cleaning glasses owe their unique properties to a thin layer of titanium oxide (TiO2 ) able to degrade organic matter when exposed to UV light. The glass samples demonstrated photocatalytic activity towards a model Volatile Organic Compound (VOC), i.e. 2-propanol, and a representative stain molecule, i.e. methylene blue (MB), analyzed at a GC-FID and a UV–vis spectrophotometer, respectively. PAC was more active than PAB towards 2-propanol oxidation under ultraviolet irradiation. Similarly, PAC showed the best reactivity in the degradation of pre-adsorbed MB under simulated solar irradiation. However, comparable performance was found for 2-propanol degradation under simulated solar irradiation. Moreover, using building energy modeling, the energy saving potential of different glazing configurations of PAB and PAC was simulated for buildings in different climatic conditions. The results were compared with those of the Pilkington Optifloat glass, which has no TiO2 coating. The best performance was obtained with the double-glazed PAB configuration. The present study is the first work on assessing the performance of self-cleaning glasses, both as regards energy efficiency and photocatalytic properties. These two types of functionality are equally important but usually evaluated separately, preventing the assessment of the performance as a whole. The clear picture of the overall performance provided in this work for two widespread commercial functionalized glasses may serve as framework for comparing new emerging self-cleaning glasses with existing benchmarks.